Ulib: library management system with data analytics - Wan Abas, Wan Nur Atiqah Humaira (2025)
University libraries play a critical role in supporting students' academic growth by offering access to a wide range of academic materials. The adoption of Library Management Systems (LMS) also revolutionises the way they operate, from relying on index cards and handwritten logs to using a platform that support various functionalities including cataloguing, storing and managing resources. Despite these advancements, university libraries still face challenges such as declining usage of printed books as students struggle to navigate large collections and remain unaware of the valuable materials. Librarians also lack analytical insights to align book collections with students’ needs. Therefore, this project aims to develop an LMS that employs descriptive data analytics to enhance access to library resources and promote student engagement with printed materials. The methodology implemented in this project is Feature-Driven Development (FDD), an iterative and feature-focused approach while technologies used are PHP for the backend and HTML, CSS, and JavaScript for the frontend. Chart.js is used for data visualization while MySQL is for database management. Key features include book recommendations, analytics dashboards, and reservation module. All testing showed positive results, confirming the system is working and user-friendly. The future suggestion includes mobile app development, support for digital materials, and integration of predictive and prescriptive analytics. In conclusion, the system helps promotes the usage of printed books among students.